IL-22BP production is heterogeneously distributed in Crohn’s disease - Fantou, Aurélie; Lagrue, Eric; Laurent, Thomas; Delbos, Laurence; Blandin, Stéphanie; Jarry, Anne; Beriou, Gaëlle; Braudeau, Cécile; Salabert, Nina; Marin, Eros; Moreau, Aurélie; Podevin, Juliette; et al. (Frontiers in Immunology, 2022)
Crohn’s disease (CD), a form of inflammatory bowel disease (IBD), is characterized by impaired epithelial barrier functions and dysregulated mucosal immune responses. IL-22 binding protein (IL-22BP) is a soluble inhibitor regulating IL-22 bioactivity, a cytokine proposed to play protective roles during CD. We and others have shown that IL-22BP is produced in IBD inflamed tissues, hence suggesting a role in CD. In this work, we extended the characterization of IL-22BP production and distribution in CD tissues by applying enzyme-linked immunosorbent assays to supernatants obtained from the culture of endoscopic biopsies of patients, and reverse transcription-quantitative polymerase chain reaction on sorted immune cell subsets. We reveal that IL-22BP levels are higher in inflamed ileums than colons. We observe that in a cell-intrinsic fashion, populations of mononuclear phagocytes and eosinophils express IL-22BP at the highest levels in comparison to other sources of T cells. We suggest the enrichment of intestinal eosinophils could explain higher IL-22BP levels in the ileum. In inflamed colon, we reveal the presence of increased IL-22/IL22BP ratios compared to controls, and a strong correlation between IL-22BP and CCL24. We identify monocyte-derived dendritic cells (moDC) as a cellular subtype co-expressing both cytokines and validate our finding using in vitro culture systems. We also show that retinoic acid induces the secretion of both IL-22BP and CCL24 by moDC. Finally, we report on higher IL-22BP levels in active smokers. In conclusion, our work provides new information relevant to therapeutic strategies modulating IL-22 bioactivity in CD, especially in the context of disease location.